Digital Data Security Literacy in College Students: An Analysis of Awareness and Behavior in Facing Cyber Threats in the Digital Age - Alif Alfi Takdir; Devi Miftahul Jannah (Sakura Digital Nusantara, 2025)
Digital data security is a crucial issue in the era of modern technology, especiallyfor students who are vulnerable to cyber threats. This study aims to analyze theeffect of digital data security literacy on students' awareness and behavior inprotecting personal data. The research was conducted with a quantitative methodusing a cross-sectional design, involving 107 students as respondents. Data wereobtained through a Likert scale-based questionnaire and analyzed descriptivelyusing Microsoft Excel and Jamovi. The results showed that the user education andawareness aspect had the highest average (3.82), reflecting students' goodunderstanding of the importance of maintaining data confidentiality. However,the data access aspect had the lowest average score (3.60), indicating the need forimprovement in controls over personal data access. These findings are relevant toprevious literature, which confirms the importance of digital security educationin improving literacy and awareness of cyber threats. This research provides newinsights that can serve as a basis for developing more effective digital securityeducation programs in educational institutions. By improving digital data securityliteracy, students are expected to be better able to protect their data from threatsin the digital era.